The Buddhist and the Ethicist : Conversations on Effective Altruism, Engaged Buddhism, and How to Build a Better World - Singer, Peter, 1946-; Zhaohui, Shi, 1957- (Boulder : Shambhala, 2023)
"This eye-opening read spans the foundations of ethics and key Buddhist concepts. Professor Peter Singer is a world-renowned moral philosopher and preeminent voice in bioethics whose writings have helped shape the animal rights and effective altruism movements. Venerable Shih Chao-Hwei of Taiwan is a Buddhist monastic and social activist who's been a key figure in the Buddhist gender equality movement. This unlikely duo came together in conversation at a meditation retreat center in 2016 and continued discussions in writing. They shed light on the intersection of philosophy, religion, and day-to-day life"--
The Foundations of Ethics -- Key Buddhist Concepts: Karma and Nirvana -- Women and Equality -- Sexuality -- Embryo Research and Abortion -- Animal Welfare -- Euthanasia and Suicide -- The Death Penalty and Killing in War.
Includes index.
Keywords: Buddhist ethics